Eating difficulties among Nigerian community-dwelling stroke survivors: prevalence, correlates, and association with quality of life - Adekola B. Ademoyegun; Adebukola G. Ibitoye; Wasiu A. Rasaq; Oluwafunmilayo A. Adeniyi; David O. Fabuluje; Israel A. Ojo; Taofeek O. Awotidebe; Chidozie E. Mbada (BMC Public Health)
Abstract Background Eating ability is central to human existence and survival, societal acceptance, life satisfaction, and social participation. Although eating difficulties (EDs) are common after stroke, few studies are reporting their impact on the quality of life (QoL) of stroke survivors. This study aimed to assess the prevalence, correlates, and association of EDs with QoL among stroke survivors. Methods A cross-sectional study on 233 (Mean age: 59.6 ± 10.9 years; 52.8% female) Nigerian community-dwelling stroke survivors attending rehabilitation at three public hospitals was conducted. The Minimal Eating Observation Form– version II and WHOQOL-BREF were used to collect data on EDs and QoL respectively. Socio-demographic, stroke-related, and clinical characteristics of patients were assessed using structured questionnaires. The association of EDs with each domain of WHOQOL-BREF (physical health, psychological health, social relationships, environmental health, perceived health status, and overall QoL) was assessed with hierarchical regression analyses. Results The majority (60.9%) of stroke survivors had at least one form of ED. Among the three types of EDs assessed, difficulty with energy/appetite (45.1%) was the most prevalent, followed by difficulty with ingestion (43.8%) and deglutition (40.8%). The results showed that EDs were associated with haemorrhagic stroke (r = 0.158; p = 0.016), right-sided hemiplegia (r = 0.172; p = 0.008), increasing stroke severity (r = 0.466; p < 0.001), increasing co-morbidity (r = 0.384; p < 0.001), poor oral health (r = 0.511; p < 0.001), poor mental health (r = 0.260; p < 0.001), poor affected grip strength (r= -0.157; p = 0.016), poor nutritional status (r= -0.362; p < 0.001), low functional ability (r= -0.415; p < 0.001), and low social support (r= -0.257; p < 0.001). After adjustments, EDs independently explained 10.7% of the variance in psychological health (β= -0.467; p < 0.001), 4.7% in social relationships (β= -0.308; p < 0.001), 2.4% in perceived health status (β= -0.221; p = 0.002), and 7.4% in overall QoL (β= -0.383; p < 0.001). However, the variance accounted for by EDs in physical and environmental health domains was insignificant. Conclusion The prevalence of EDs among Nigerian community-dwelling stroke survivors is high, which is associated with many stroke-related and clinical factors. Meanwhile, increasing in EDs is independently associated with reduced QoL among stroke survivors using WHOQOL-BREF. Emphasis on screening and management of EDs in stroke rehabilitation protocols may assist in improving survivors’ QoL.